Analyzing the Effectiveness of Commercial Low-Cost Photogrammetry Systems in the 3D Modeling of Historical Monuments - الخليل, عمر; علي, احمد (Latakia University Journal -Engineering Sciences Series, 2021)
During the past few years, new developments have occurred in the field of 3D photogrammetric modeling of historical monuments. One of these developments is the expansion of 3D photogrammetric modeling cost-effective licensed software, such as Agisoft Metashape, into the practical and affordable world. This type of SfM (Structure from Motion) software offers the world of 3D modelling of cultural heritage a powerful tool for documentation and visualization. This paper presents a methodology for evaluating the effectiveness of a range of commercial SfM photogrammetry systems when applied in the 3D modeling of historical monuments. The monument to which these systems were applied is the principal façade of Safita Tower, a medieval structure in Safita, north-western Syria.. The applied photogrammetric systems consist of the Nikon Coolpix P100 10 MP digital camera, the commercial software Agisoft Metashape, 3DF Zephyr Aerial and Pix4D Mapper. The resulted 3D point clouds were compared with an available dense point cloud acquired by a laser scanner. This comparison proved that the low-cost SfM photogrammetry is an accurate methodology to 3D modeling historical monuments.